A Brief Exploration of the Goal Congruence of Net Realization Value. - McKeown, James C. (The Accounting Review, 1973)
The article explores the goal congruence of net realizable value (NRV). The NRV model would have various properties after the evaluation of a decision at the end of period T to hold an asset. A correct decision was made if the NRV income for period T+1 is positive. The NRV income for period T+1 will be negative if an incorrect decision was made at time T. The decision at the end of period T to hold an asset may have been correct is the NRV income for period T+1 is negative. However, if it was correct, another condition must hold.